Porous cracking catalyst, preparation method thereof and application of porous cracking catalyst in reaction for preparing low-carbon olefin from waste plastics

By developing porous cracking catalysts, including SAPO-18 molecular sieve, ultra-large pore silica gel and modified oxides, for the direct catalytic cracking reaction of waste plastics, the problem of low low-carbon olefin content in the existing technology has been solved and efficient production has been achieved Effect of light olefins.

CN119327508AActive Publication Date: 2025-01-21CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310876314.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-17
Publication Date
2025-01-21
Estimated Expiration
2043-07-17

AI Technical Summary

Technical Problem

In the prior art, the content of low-carbon olefins recovered in chemical recycling and utilization of waste plastics is relatively small, making it difficult to effectively produce pure and high-quality low-carbon olefins.

Method used

Develop a porous cracking catalyst, including SAPO-18 molecular sieve, ultra-large pore silica gel and modified oxide, to achieve efficient production of low-carbon olefins through its direct catalytic cracking reaction in waste plastics.

Benefits of technology

The porous cracking catalyst can effectively improve the conversion rate of waste plastics and the selectivity of low-carbon olefins, solve the problems of waste plastic recycling and low-carbon olefin production, and at the same time have good economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327508A_ABST
    Figure CN119327508A_ABST
Patent Text Reader

Abstract

The invention relates to the field of catalysts and the field of high polymer material recycling, and discloses a porous cracking catalyst, a preparation method thereof and application of the porous cracking catalyst in a reaction for preparing low-carbon olefin from waste plastics. The porous cracking catalyst comprises an SAPO-18 molecular sieve, super-macroporous silica gel and a modified oxide, and on the basis of the total weight of the porous cracking catalyst, the SAPO-18 molecular sieve accounts for 28-60 wt%, the super-macroporous silica gel accounts for 30-70 wt%, and the modified oxide accounts for 2-10 wt%; the specific surface area of the porous cracking catalyst is 380-450 m < 2 > / g, the pore volume is 0.68-1.05 mL / g, the pore size distribution is three-peak distribution, and the most probable pore sizes corresponding to the three peaks are 0.38-0.45 nm, 2-4.5 nm and 15-45 nm respectively. The porous cracking catalyst is applied to waste plastics, so that the problem of waste plastic recovery is solved, and the yield of important chemical raw material low-carbon olefin is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalysts and polymer material recycling, and in particular to a porous cracking catalyst and a preparation method thereof, as well as an application in the reaction of preparing low-carbon olefins from waste plastics. Background Art

[0002] Since the advent of plastic products in the 20th century, they have been widely used in various fields around the world with the characteristics of light weight, high strength, corrosion resistance, good chemical stability, easy processing, and beautiful and practical. However, plastics are difficult to degrade naturally. Although conventional landfill technology requires little investment and is simple to operate, it will occupy a large amount of land and cause land pollution. Although incineration technology can achieve the reduction requirements and recover some energy at the same time, this process is prone to release a large amount of hydrocarbons, nitrides, sulfides and highly toxic substances, which directly threaten human and ecological health. Therefore, the recycling and high-value utilization of waste plastics as a measure to save energy and protect the environment has been widely valued by countries around the world. The methods for recycling and utilizing waste plastics mainly include classified recycling, preparation of monomer raw materials, production of clean fuel and use for power generation.

[0003] my country's plastics industry is one of the pillar industries of the national economy. At present, my country has entered the ranks of the world's major plastics countries. Under the policy background of the new plastic restriction order, the sharp decline in imports, and garbage classification, my country's waste plastic recycling companies are gradually getting rid of the old path of extensive expansion in the past, and gradually examining the industrial layout with the perspective of green development. Continue to deepen cooperation with environmental protection and sanitation companies to gradually achieve the goal of green, low-carbon and circular development. Large-scale waste plastic recycling companies with standardized operations will gradually further refine the recycled waste plastics, continue to develop and apply new technologies and new products for waste plastics, gradually expand the application field of waste plastics, and increase the added value of recycled plastic products. In the existing technology, the chemical recycling scheme for waste plastics is mainly waste plastic cracking technology. There are three basic methods for waste plastic cracking, namely: thermal cracking (one-stage method), catalytic cracking (one-stage method) and thermal cracking-catalytic modification (two-stage method). The earliest developed waste plastic cracking technology is thermal cracking technology. This technology refers to a thermal conversion process in which a thermochemical decomposition reaction occurs under high temperature and anaerobic conditions to convert large molecular weight organic matter in waste plastic products into small molecular weight liquids, fuel gas, coke and other substances. The reaction temperature of this process is generally controlled at 350-900°C. If a catalyst is added during the thermal cracking process, it is a catalytic thermal cracking technology, which can not only reduce the cracking temperature, but also improve product performance. The thermal cracking-catalytic reforming method is an improvement on the catalytic cracking method. After the waste plastics are thermally cracked, a catalyst is used to catalytically reform the cracking gas. This method has higher product quality, more flexible operation and lower operating costs than the thermal cracking method and the catalytic cracking method, but the process is more complicated.

[0004] Cracking technology has wide flexibility in treating waste plastics and good energy recovery, and is one of the waste plastic treatment technologies with broad application prospects. In the prior art, the products produced by the one-step thermal cracking method and the one-step catalytic cracking method are mainly fuel oil, and only a small amount of low-carbon olefins (ethylene, propylene, butene) can be obtained. If a large amount of low-carbon olefins are required, a two-stage method of thermal cracking-catalytic modification is required. Therefore, exploring a new chemical recovery process to produce pure and high-quality final products is an important research direction for plastic waste treatment. Summary of the invention

[0005] The purpose of the present invention is to provide a porous cracking catalyst and a preparation method thereof as well as an application in the reaction of preparing light carbon olefins from waste plastics in order to address the current problem that the content of light carbon olefins recovered in the current chemical recycling of waste plastics is low. The porous cracking catalyst is applied to waste plastics to provide a new approach for the one-step catalytic conversion and utilization of waste plastics, thereby solving the problem of recycling waste plastics and increasing the production of light carbon olefins, which are important chemical raw materials.

[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a porous cracking catalyst, wherein the porous cracking catalyst comprises SAPO-18 molecular sieve, ultra-large pore silica gel and modified oxide, and based on the total weight of the porous cracking catalyst, the content of the SAPO-18 molecular sieve is 28-60% by weight, the content of the ultra-large pore silica gel is 30-70% by weight, and the content of the modified oxide is 2-10% by weight;

[0007] The specific surface area of ​​the porous cracking catalyst is 380-450m 2 / g, the pore volume is 0.68-1.05mL / g, the pore size distribution is a trimodal distribution, and the most probable pore sizes corresponding to the three peaks are 0.38-0.45nm, 2-4.5nm and 15-45nm, respectively.

[0008] A second aspect of the present invention provides a method for preparing the aforementioned porous cracking catalyst, wherein the preparation method comprises:

[0009] (1) mixing a template, an aluminum source, a phosphorus source, a silicon source and water and performing a contact reaction to obtain a gel mixture; performing a first crystallization treatment on the gel mixture to obtain a mixed slurry, mixing the mixed slurry with ultra-large pore silica gel and performing a second crystallization treatment, and separating, washing, drying and calcining the product after the crystallization treatment to obtain a mixed molecular sieve;

[0010] (2) The mixed molecular sieve is immersed in an aqueous solution containing a modified oxide precursor, and the solid product after removing moisture is dried and calcined to obtain a porous cracking catalyst.

[0011] The third aspect of the present invention provides an application of the aforementioned porous cracking catalyst in the direct catalytic cracking of waste plastics to produce light olefins.

[0012] Through the above technical solution, compared with the prior art, the technical solution of the present invention has the following advantages:

[0013] (1) The porous cracking catalyst provided by the present invention includes SAPO-18 zeolite molecular sieve with acidic centers on the surface and ultra-large pore silica gel with double-pore mesoporous channels, which has a stable structure and good high temperature resistance, and is conducive to the diffusion of raw material and product molecules during the cracking reaction.

[0014] (2) In the preparation process of the porous cracking catalyst provided by the present invention, the mother liquor after the primary crystallization of SAPO-18 molecular sieve is mixed with the ultra-large pore silica gel after ball milling, and then secondary crystallization is performed to directly obtain a porous cracking catalyst in which the micropores and mesopores are evenly distributed.

[0015] (3) The porous cracking catalyst provided by the present invention can convert waste plastics into light olefins in one step when used for direct catalytic cracking of waste plastics to produce light olefins, which is a new method for chemical recycling of waste plastics. It not only solves the problem of recycling waste plastics, but also increases the production of light olefins, an important chemical raw material, and has good economic benefits.

[0016] (4) When the porous cracking catalyst provided by the present invention is used for the direct catalytic cracking of waste plastics to produce light olefins, the process conditions are mild, the operation is easy, and the requirements for the reaction device are not high.

[0017] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings:

[0019] Figure 1 is a pore size distribution diagram of super-macroporous silica gel A prepared in Example 1 of the present invention;

[0020] Figure 2 This is a pore size distribution diagram of the porous cracking catalyst A prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0021] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0022] As mentioned above, the first aspect of the present invention provides a porous cracking catalyst, wherein the porous cracking catalyst comprises SAPO-18 molecular sieve, ultra-large pore silica gel and modified oxide, and based on the total weight of the porous cracking catalyst, the content of the SAPO-18 molecular sieve is 28-60% by weight, the content of the ultra-large pore silica gel is 30-70% by weight, and the content of the modified oxide is 2-10% by weight;

[0023] The specific surface area of ​​the porous cracking catalyst is 380-450m 2 / g, the pore volume is 0.68-1.05mL / g, the pore size distribution is a trimodal distribution, and the most probable pore sizes corresponding to the three peaks are 0.38-0.45nm, 2-4.5nm and 15-45nm, respectively.

[0024] The inventor of the present invention found that: in the prior art, there is no process for directly catalytic cracking of waste plastics to produce low-carbon olefins (including ethylene, propylene, butene), and the purpose of the present invention is to solve this problem. According to the inventor's understanding of the physicochemical properties of heterogeneous catalysts, the catalyst used for catalytic cracking of waste plastics to directly prepare low-carbon olefins should have a certain acidity but the acidity should not be too strong. In addition, the catalyst for catalytic cracking of waste plastics needs to have good thermal stability. SAPO-18 molecular sieve not only has surface acidic sites, but also has good thermal stability (the crystal phase can still remain stable after high-temperature roasting at 550°C), and can be used as a catalyst for catalytic cracking reaction of waste plastics after appropriate modification. However, the pore size of SAPO-18 molecular sieve is generally about 0.4nm, which seriously limits the practical application of SAPO-18 molecular sieve catalyst, mainly because SAPO-18 is a microporous molecular sieve, its pore size is small, the pore volume is also small, and the molecular weight of the waste plastic product is large, and the molecular chain is also long. In the cracking reaction of waste plastic products, it is difficult for larger reactant molecules and product molecules to diffuse in narrow channels, which not only affects the contact between reactants and active centers, but also easily leads to side reactions such as deep dehydrogenation, which in turn leads to a decrease in catalyst performance. Compared with microporous molecular sieves, ultra-large pore silica gel materials have double pore channels with larger pore sizes (the most probable pore diameters are 2-5nm and 20-50nm, respectively) and large pore volumes (up to 1.0cm 3 / g or more), which is very suitable for catalytic reactions involving macromolecules. However, super-large pore silica gel is a full silicon material, and only contains a small amount of silanol on the surface, and the acidity is extremely weak, which is not suitable for being used alone as a catalyst to catalyze the cracking reaction of waste plastics. The inventors of the present invention found in the development and research of waste plastic cracking catalysts that if the structural advantages of super-large pore silica gel and the surface acidic centers of zeolite molecular sieves are comprehensively utilized, and a certain amount of super-large pore silica gel is mixed with SAPO-18 molecular sieves, the pore volume of the catalyst can be effectively increased, and the internal diffusion performance in the reaction can be significantly improved. When used as a cracking catalyst in the catalytic conversion reaction of waste plastics, it can not only effectively improve the activity of the cracking catalyst, but also increase the selectivity of light olefins.

[0025] According to the present invention, preferably, based on the total weight of the porous cracking catalyst, the content of the SAPO-18 molecular sieve is 32-56% by weight, the content of the ultra-large pore silica gel is 35-65% by weight, and the content of the modified oxide is 3-9% by weight; more preferably, based on the total weight of the porous cracking catalyst, the content of the SAPO-18 molecular sieve is 36-52% by weight, the content of the ultra-large pore silica gel is 40-60% by weight, and the content of the modified oxide is 4-8% by weight. In the present invention, the use of the aforementioned specific content of each component can make the prepared porous cracking catalyst have better catalytic activity and higher selectivity for light olefins when used for the direct catalytic cracking of waste plastics to prepare light olefins.

[0026] According to the present invention, preferably, the specific surface area of ​​the porous cracking catalyst is 388-445m 2 / g, pore volume of 0.76-1mL / g, pore size distribution of trimodal distribution, and the most probable pore sizes corresponding to the three peaks are 0.39-0.44nm, 2.5-4nm and 20-38nm respectively; more preferably, the specific surface area of ​​the porous cracking catalyst is 394-440m 2 / g, pore volume is 0.84-0.93mL / g, pore size distribution is trimodal distribution, and the most probable pore sizes corresponding to the three peaks are 0.4-0.42nm, 2.8-3.4nm and 25-32nm respectively. In the present invention, when the porous cracking catalyst has the aforementioned specific structural parameters, it can be used for the direct catalytic cracking of waste plastics to prepare light olefins with better catalytic activity and higher light olefin selectivity.

[0027] According to the present invention, the modified oxide is selected from alkaline earth metal oxides; preferably, the modified oxide is selected from one or more of calcium oxide, magnesium oxide, strontium oxide and barium oxide.

[0028] According to the present invention, the specific surface area of ​​the ultra-large pore silica gel is 200-500m2 / g, the pore volume is 1-2mL / g, the pore size is bimodal distribution, the first most probable pore size is 2-5nm, and the second most probable pore size is 20-50nm.

[0029] According to the present invention, the method for preparing the ultra-macroporous silica gel comprises:

[0030] In the presence of butanol and propylene glycol, an inorganic silicon source is contacted with an acid agent, and the obtained mixture is filtered and washed to obtain a silica gel filter cake; the silica gel filter cake is then dried, calcined and ball-milled to obtain ultra-large-porous silica gel.

[0031] According to the present invention, the butanol may be one or more of n-butanol, sec-butanol and isobutanol; preferably n-butanol.

[0032] According to the present invention, the inorganic silicon source is selected from one or more of water glass, sodium metasilicate and silica sol, preferably water glass.

[0033] According to the present invention, the acid agent can be any conventional substance or mixture (such as a solution) that can be used to adjust the pH value; preferably, the acid agent is selected from at least one aqueous solution of hydrochloric acid, sulfuric acid, nitric acid and hydrobromic acid; more preferably, the acid agent is an aqueous sulfuric acid solution.

[0034] According to the present invention, the weight ratio of the inorganic silicon source, acid agent, butanol and glycerol is 1: (0.05-0.5): (0.02-0.6): (0.02-0.6), preferably 1: (0.1-0.3): (0.06-0.4): (0.06-0.4).

[0035] According to the present invention, the conditions for contacting the inorganic silicon source with the acid agent may include: a temperature of 15-40° C. and a time of 1-3 hours; preferably, in order to achieve a better mixing effect, rapid stirring or ultrasonic means may be used to improve the mixing efficiency during the contact (hydrolysis and gel preparation) of the inorganic silicon source with the acid agent.

[0036] According to the present invention, there are no special requirements for the filtering method, and it can be a filtering method known in the art, including gravity filtration, pressure filtration, vacuum filtration or centrifugal filtration. Preferably, the filtering process specifically includes: using a suction bottle, vacuuming the bottom side of the funnel or filtering using a centrifugal filter.

[0037] According to the present invention, the washing conditions are not particularly limited. For example, the washing process may include: obtaining a solid product after filtration, repeatedly washing the solid product with distilled water (the number of washing times may be 2-10) and then filtering.

[0038] According to the present invention, the drying conditions include: drying temperature of 60-150° C., and drying time of 1-30 h; preferably, the temperature is 90-130° C., and the time is 5-16 h.

[0039] According to the present invention, the calcination conditions include: calcination temperature of 450-700° C., calcination time of 3-20 h; preferably, the temperature is 500-650° C., and the time is 6-12 h.

[0040] According to the present invention, the ball milling is carried out in a ball mill, wherein the diameter of the grinding balls in the ball mill can be 2-3 mm; the number of grinding balls can be reasonably selected according to the size of the ball mill jar, and for a ball mill jar of 100-300 mL, 2-8 grinding balls can usually be used; the material of the grinding balls is agate or polytetrafluoroethylene, preferably agate. The conditions of the ball milling include: the rotation speed of the grinding balls can be 200-600r / min, preferably 300-500r / min; the temperature in the ball mill jar can be 30-90°C, preferably 40-80°C; the ball milling time can be 5-50h, preferably 8-24h.

[0041] A second aspect of the present invention provides a method for preparing the aforementioned porous cracking catalyst, wherein the preparation method comprises:

[0042] (1) mixing a template, an aluminum source, a phosphorus source, a silicon source and water and performing a contact reaction to obtain a gel mixture; performing a first crystallization treatment on the gel mixture to obtain a mixed slurry, mixing the mixed slurry with ultra-large pore silica gel and performing a second crystallization treatment, and separating, washing, drying and calcining the product after the crystallization treatment to obtain a mixed molecular sieve;

[0043] (2) The mixed molecular sieve is immersed in an aqueous solution containing a modified oxide precursor, and the solid product after removing moisture is dried and calcined to obtain a porous cracking catalyst.

[0044] The inventors of the present invention have found that mixing a certain amount of ultra-large pore silica gel with SAPO-18 molecular sieves can increase the pore volume of the catalyst and improve the internal diffusion performance in the reaction. However, if the two prepared molecular sieves are mechanically mixed, the micropore channels and mesopore channels in the obtained mixed molecular sieve are unevenly distributed, and the effect of improving the diffusion performance is not significant enough. In the present invention, the inventors mixed the mother liquor after the primary crystallization of the SAPO-18 molecular sieve with the ultra-large pore silica gel after ball milling, and carried out secondary crystallization to obtain a porous cracking catalyst. The micropore channels and mesopore channels in the composite molecular sieve obtained by this method are evenly distributed, and the catalytic activity is high and the selectivity of low-carbon olefins is high when used for the catalytic cracking reaction of waste plastics.

[0045] According to the present invention, in step (1), the template is N,N-diisopropylethylamine.

[0046] According to the present invention, in step (1), the aluminum source is selected from one or more of pseudo-boehmite, aluminum hydroxide, alkaline aluminum sol, aluminum isopropoxide, basic aluminum acetate, gibbsite and boehmite, preferably one or more of pseudo-boehmite, aluminum hydroxide, alkaline aluminum sol and aluminum isopropoxide, more preferably pseudo-boehmite.

[0047] According to the present invention, in step (1), the phosphorus source is an inorganic acid or acid salt containing phosphorus, preferably one or more of phosphoric acid, phosphorous acid, diammonium phosphate and monoammonium hydrogen phosphate, more preferably phosphoric acid.

[0048] According to the present invention, in step (1), the silicon source is an organic silicon source and / or an inorganic silicon source, preferably one or more of tetramethyl silicate, tetraethyl silicate, tetraisopropyl silicate, tetrabutyl silicate, silica sol, water glass and white carbon black, more preferably silica sol.

[0049] According to the present invention, in step (1), the molar ratio of the aluminum source (in terms of Al2O3), the silicon source (in terms of SiO2), the phosphorus source (in terms of P2O5), the template and water is 1: (0.1-2): (0.2-2.5): (0.5-3): (10-150), preferably 1: (0.3-1): (0.5-1.2): (1-2): (30-80).

[0050] According to the present invention, in step (1), the contact reaction conditions include: temperature of 20-100°C, preferably 40-80°C; time of 1-10h, preferably 2-6h. Preferably, in order to achieve a better mixing effect, rapid stirring or ultrasonic means can be used to improve the mixing efficiency during the contact reaction.

[0051] According to the present invention, in step (1), the conditions for the first crystallization include: temperature of 140-200° C., preferably 160-180° C.; time of 2-24 h, preferably 6-16 h.

[0052] According to the present invention, in step (1), the weight ratio of the ultra-large pore silica gel to the mixed slurry is 1:(2-15), preferably 1:(3-10).

[0053] According to the present invention, in step (1), the conditions for the second crystallization include: temperature of 140-200° C., preferably 160-180° C.; time of 20-100 h, preferably 48-72 h.

[0054] According to the present invention, in step (1), there is no special requirement for the separation method, which can be a separation method known in the art, including gravity filtration, pressure filtration, vacuum filtration or centrifugal filtration. Preferably, the separation process specifically includes: using a suction bottle, vacuuming the bottom side of the funnel or filtering using a centrifugal filter.

[0055] According to the present invention, in step (1), there is no special requirement for the method of washing the solid product. For example, the solid product can be washed with deionized water, the volume ratio of deionized water to solid product can be 5-20, and the number of washing times can be 2-8 times.

[0056] According to the present invention, in step (1), the drying conditions include: temperature of 60-150° C., preferably 80-130° C.; time of 1-30 h, preferably 3-20 h.

[0057] According to the present invention, in step (1), the calcination conditions include: temperature of 450-650° C., preferably 500-600° C.; time of 5-50 h, preferably 8-30 h.

[0058] According to the present invention, in step (2), the modified oxide precursor comprises an inorganic salt of an alkaline earth metal; preferably, the alkaline earth metal is selected from one or more of calcium, magnesium, strontium and barium.

[0059] According to the present invention, in step (2), the mass concentration of the aqueous solution containing the modified oxide precursor is 0.3-5%, preferably 0.5-4%.

[0060] According to the present invention, in step (2), the weight ratio of the mixed molecular sieve to the aqueous solution containing the modified oxide precursor is 1:(5-20), preferably 1:(8-16).

[0061] According to the present invention, in step (2), the immersion conditions include: temperature of 10-100° C., preferably 20-90° C.; time of 0.5-20 h, preferably 2-12 h. Preferably, in order to achieve a better mixing effect, rapid stirring or ultrasonic means can be used to improve the mixing efficiency during the contact reaction.

[0062] According to the present invention, in step (2), there is no particular requirement for the method of removing water, and it may be a method known in the art, such as using a rotary evaporator or heating and evaporating during stirring.

[0063] According to the present invention, in step (2), the drying conditions include: temperature of 70-150° C., preferably 90-120° C.; time of 2-30 h, preferably 4-20 h.

[0064] According to the present invention, in step (2), the calcination conditions include: temperature of 500-700° C., preferably 550-650° C.; time of 3-20 h, preferably 5-12 h.

[0065] The third aspect of the present invention provides an application of the aforementioned porous cracking catalyst in the direct catalytic cracking of waste plastics to produce light olefins.

[0066] According to the present invention, the application comprises: under specific conditions, waste plastic powder or particles are contacted with the porous cracking catalyst to react.

[0067] According to the present invention, the contact conditions include: temperature of 420-580° C., pressure of 0.01-1 MPa, and contact time of 0.5-12 h.

[0068] According to the present invention, the weight ratio of the porous cracking catalyst to the waste plastic powder or particles is 1:(0.5-50).

[0069] The present invention will be described in detail below through examples.

[0070] In the following examples and comparative examples:

[0071] The pore structure parameter analysis of the samples was carried out on an ASAP2020-M+C adsorption instrument purchased from Micromeritics, Inc., USA. The samples were vacuum degassed at 350°C for 4 hours before measurement, and the specific surface area of ​​the samples was calculated using the BET method, and the pore volume was calculated using the BJH model.

[0072] The elemental analysis experiment of the samples was carried out on an EagleⅢ energy dispersive X-ray fluorescence spectrometer produced by EDAX, USA.

[0073] The drying oven was produced by Shanghai Yiheng Scientific Instrument Co., Ltd., model DHG-9030A.

[0074] The muffle furnace is produced by CARBOLITE, model CWF1100.

[0075] Other reagents used in the examples and comparative examples were purchased from Sinopharm Chemical Reagent Co., Ltd. and were of analytical purity.

[0076] Example 1

[0077] This embodiment is intended to illustrate the porous cracking catalyst prepared by the present invention and its application in the reaction of producing light olefins from waste plastics.

[0078] (1) Preparation of ultra-macroporous silica gel

[0079] 50g of 15 wt% water glass, 10g of 12 wt% sulfuric acid aqueous solution, 10g of n-butanol and 10g of propylene glycol were mixed at 25°C and contacted for 2.0h under stirring conditions. A white solid substance was obtained by suction filtration, and the solid substance was washed 8 times with distilled water to obtain a silica gel filter cake. The silica gel filter cake was dried at 110°C for 12h, calcined at 550°C for 8h, and then placed in a 100mL ball mill, wherein the ball mill was made of polytetrafluoroethylene, the grinding balls were made of agate, the diameter of the grinding balls was 3mm, the number was 4, and the rotation speed was 400r / min. The ball mill was closed and ball milled at 60°C in the ball mill for 16h to obtain ultra-large pore silica gel A.

[0080] The specific surface area of ​​super-large pore silica gel A is 361m 2 / g, and the pore volume is 1.7ml / g.

[0081] Figure 1 is the average pore size distribution diagram of the super-large pore silica gel A prepared in Example 1. Figure 1 It can be seen that the pore size of the material is bimodal, with the first most probable pore size being 3.3 nm and the second most probable pore size being 32 nm.

[0082] (2) Preparation of porous cracking catalyst

[0083] At 60°C, firstly, pseudo-boehmite powder of model P-DF-03-LS (produced by Shandong Aluminum Co., Ltd., with a specific surface area of ​​257 m 2 / g, pore volume 0.32cm 3 / g) was mixed with deionized water, and phosphoric acid was added after stirring for 1 hour. After stirring for another 1 hour, silica sol was added. After stirring evenly, the template agent N,N-diisopropylethylamine was slowly added dropwise. In the mixed system, n(Al2O3):n(SiO2):n(P2O5):n(C8H 19 N):n(H2O) in a molar ratio of 1:0.6:0.9:1.6:60. After the template agent is added dropwise, the mixed system is stirred for 1 hour at 60°C to obtain a gel mixture. The gel mixture is then transferred to a hydrothermal autoclave with a polytetrafluoroethylene liner for the first crystallization treatment. The temperature of the first crystallization treatment is 170°C and the time is 12 hours. The mixed slurry obtained after the first crystallization treatment is uniformly mixed with superporous silica gel A (the weight ratio of superporous silica gel to mixed slurry is 1:6.4) and subjected to a second crystallization treatment. The temperature of the second crystallization treatment is 170°C and the time is 60 hours. After the crystallization is completed, the solid product obtained by centrifugal filtration is washed 6 times with deionized water, the solid product is dried at 110°C for 10 hours, and then calcined at 550°C for 16 hours to obtain a mixed molecular sieve A.

[0084] 1.8 g of calcium nitrate was dissolved in 100 g of deionized water, 9.4 g of the above-mentioned mixed molecular sieve A was added, and the mixture was stirred at 50° C. for 6 h. The solid product obtained after removing moisture using a rotary evaporator was dried at 110° C. for 12 hours and calcined at 600° C. for 8 hours to obtain a porous cracking catalyst A.

[0085] Based on the total weight of the porous cracking catalyst A, the content of SAPO-18 molecular sieve is 44% by weight, the content of ultra-large pore silica gel is 50% by weight, and the content of calcium oxide is 6%.

[0086] The specific surface area of ​​porous cracking catalyst A is 420 m 2 / g, pore volume 0.91cm 3 / g.

[0087] Figure 2 is the pore size distribution diagram of the porous cracking catalyst A prepared in Example 1. Figure 2 It can be seen that the sample has an obvious three-pore channel structure, with the most probable pore sizes of 0.41nm, 3.1nm and 28nm respectively. Among them, the channel with the most probable pore size of 0.41nm is provided by SAPO-18 molecular sieve, and the two types of mesoporous channels with the most probable pore sizes of 3.1nm and 28nm are provided by ultra-large pore silica gel. Compared with the most probable pore size of ultra-large pore silica gel A, the two types of mesoporous channels of porous cracking catalyst A are slightly smaller. This is mainly due to the fact that during the secondary crystallization process, a small part of the SAPO-18 molecular sieve with smaller particles entered the ultra-large pore silica gel channel and caused slight blockage.

[0088] (3) Evaluation of the reaction performance of direct conversion of waste plastics to light olefins

[0089] The catalytic cracking reaction performance of waste plastics using porous cracking catalyst A was evaluated in a fixed bed reactor. The loading amount of porous cracking catalyst A was 6.0 g, the loading amount of polyethylene waste plastic was 40.0 g, the reaction temperature was 480°C, the reaction pressure was 0.1 MPa, the reaction time was 2 hours, and after the product was cooled and the gas-liquid was separated, the gas composition was analyzed by an Agilent 6890N gas chromatograph equipped with an Al2O3-S capillary column and a hydrogen flame detector (FID), and the quantitative analysis was performed using a programmed temperature rise and a correction factor; the liquid composition was analyzed by an Agilent 7890A gas chromatograph equipped with a PONA column. The reaction results are shown in Table 1.

[0090] Example 2

[0091] This embodiment is intended to illustrate the porous cracking catalyst prepared by the present invention and its application in the reaction of producing light olefins from waste plastics.

[0092] (1) Preparation of ultra-macroporous silica gel

[0093] 100g of 15 wt% water glass, 30g of 12 wt% sulfuric acid aqueous solution, 6g of n-butanol and 40g of propylene glycol were mixed at 15°C and contacted for 3.0h under stirring conditions. A white solid substance was obtained by suction filtration, and the solid substance was washed 4 times with distilled water to obtain a silica gel filter cake. The silica gel filter cake was dried at 90°C for 16h, calcined at 500°C for 12h, and then placed in a 200ml ball mill, 8 agate grinding balls with a diameter of 2mm were added, the ball mill was closed, and ball milling began. The temperature in the ball mill was controlled at 80°C, the speed of the grinding balls was 300r / min, and the ball milling time was 8h to obtain ultra-large pore silica gel B.

[0094] The specific surface area of ​​super-macroporous silica gel B is 381 m 2 / g, the pore volume is 1.8ml / g, the first most probable pore diameter is 3.5nm, and the second most probable pore diameter is 36nm.

[0095] (2) Preparation of porous cracking catalyst

[0096] At 40°C, the German imported pseudo-boehmite powder (model SB, purchased from Beijing Asia Pacific Aohua Chemical Additives Co., Ltd., with a specific surface area of ​​241 m 2 / g, pore volume 0.53cm 3 / g) was mixed with deionized water, and phosphoric acid was added after stirring for 1 hour. After stirring for another 1 hour, silica sol was added. After stirring evenly, the template agent N,N-diisopropylethylamine was slowly added dropwise. In the mixed system, n(Al2O3):n(SiO2):n(P2O5):n(C8H 19 N):n(H2O) in a molar ratio of 1:0.4:0.7:1.3:50. After the template agent is added dropwise, the mixed system is stirred for 3 hours at 40°C to obtain a gel mixture. The gel mixture is then transferred to a hydrothermal kettle with a polytetrafluoroethylene liner for the first crystallization treatment. The temperature of the first crystallization treatment is 160°C and the time is 16 hours. The mixed slurry obtained after the first crystallization treatment is uniformly mixed with superporous silica gel B (the weight ratio of superporous silica gel to mixed slurry is 1:9.2) and subjected to a second crystallization treatment. The temperature of the second crystallization treatment is 160°C and the time is 72 hours. After the crystallization is completed, the solid product obtained by centrifugal filtration is washed 8 times with deionized water, the solid product is dried at 130°C for 3 hours, and then calcined at 600°C for 8 hours to obtain a mixed molecular sieve B.

[0097] 1.4 g of barium nitrate was dissolved in 80 g of deionized water, 9.2 g of the above-mentioned mixed molecular sieve B was added, and the mixture was stirred at 90° C. for 2 h. The solid product obtained after removing moisture using a rotary evaporator was dried at 120° C. for 4 hours and calcined at 650° C. for 5 hours to obtain a porous cracking catalyst B.

[0098] Based on the total weight of the porous cracking catalyst B, the content of SAPO-18 molecular sieve is 52% by weight, the content of ultra-large pore silica gel is 40% by weight, and the content of barium oxide is 8%.

[0099] The specific surface area of ​​porous cracking catalyst B is 440 m 2 / g, pore volume 0.84cm 3 / g, and the most probable pore sizes are 0.42nm, 3.2nm and 31nm respectively.

[0100] (3) Evaluation of the reaction performance of direct conversion of waste plastics to light olefins

[0101] The reaction performance of porous cracking catalyst B was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (3) of Example 1. The evaluation results are listed in Table 1.

[0102] Example 3

[0103] This embodiment is intended to illustrate the porous cracking catalyst prepared by the present invention and its application in the reaction of producing light olefins from waste plastics.

[0104] (1) Preparation of ultra-macroporous silica gel

[0105] 100g of 15 wt% water glass, 10g of 12 wt% sulfuric acid aqueous solution, 40g of n-butanol and 6g of propylene glycol were mixed at 40°C and contacted for 1.0h under stirring conditions. A white solid substance was obtained by suction filtration, and the solid substance was washed 8 times with distilled water to obtain a silica gel filter cake. The silica gel filter cake was dried at 130°C for 5h, calcined at 650°C for 6h, and then placed in a 200ml ball mill, 6 agate grinding balls with a diameter of 2.5mm were added, the ball mill was closed, and ball milling was started. The temperature in the ball mill was controlled at 40°C, the speed of the grinding balls was 500r / min, and the ball milling time was 24h to obtain ultra-large pore silica gel C.

[0106] The specific surface area of ​​super-macroporous silica gel C is 338m 2 / g, the pore volume is 1.5ml / g, the first most probable pore diameter is 3.0nm, and the second most probable pore diameter is 31nm.

[0107] (2) Preparation of porous cracking catalyst

[0108] At 80°C, firstly, the pseudo-boehmite powder of model PB-0104 (produced by Zibo Hengqi Powder New Material Co., Ltd., with a specific surface area of ​​250m 2 / g, pore volume 0.42cm 3 / g) was mixed with deionized water, and phosphoric acid was added after stirring for 0.5h. After continuing to stir for 0.5h, silica sol was added. After stirring evenly, the template agent N,N-diisopropylethylamine was slowly added dropwise. In the mixed system, n(Al2O3):n(SiO2):n(P2O5):n(C8H 19 N):n(H2O) in a molar ratio of 1:0.8:1.0:1.8:70. After the template agent is added dropwise, the mixed system is stirred for 1.0h at 80°C to obtain a gel mixture. The gel mixture is then transferred to a hydrothermal reactor with a polytetrafluoroethylene liner for the first crystallization treatment. The temperature of the first crystallization treatment is 180°C and the time is 6h. The mixed slurry obtained after the first crystallization treatment is uniformly mixed with superporous silica gel C (the weight ratio of superporous silica gel to mixed slurry is 1:4.6) and subjected to a second crystallization treatment. The temperature of the second crystallization treatment is 180°C and the time is 48h. After the crystallization is completed, the solid product obtained by centrifugal filtration is washed 4 times with deionized water, the solid product is dried at 80°C for 20h, and then calcined at 500°C for 30h to obtain a mixed molecular sieve C.

[0109] 0.8 g of strontium nitrate was dissolved in 120 g of deionized water, 9.6 g of the above-mentioned mixed molecular sieve C was added, and the mixture was stirred at 90° C. for 2 h. The solid product obtained after removing moisture using a rotary evaporator was dried at 120° C. for 4 hours and calcined at 650° C. for 5 hours to obtain a porous cracking catalyst C.

[0110] Based on the total weight of the porous cracking catalyst C, the content of SAPO-18 molecular sieve is 36% by weight, the content of ultra-large pore silica gel is 60% by weight, and the content of strontium oxide is 4%.

[0111] The specific surface area of ​​porous cracking catalyst C is 394m 2 / g, pore volume 0.93cm 3 / g, and the most probable pore sizes are 0.40nm, 2.8nm and 26nm respectively.

[0112] (3) Evaluation of the reaction performance of direct conversion of waste plastics to light olefins

[0113] The reaction performance of porous cracking catalyst C was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (3) of Example 1. The evaluation results are listed in Table 1.

[0114] Example 4

[0115] This embodiment is intended to illustrate the porous cracking catalyst prepared by the present invention and its application in the reaction of producing light olefins from waste plastics.

[0116] Ultra-large pore silica gel A was prepared in the same manner as step (1) in Example 1.

[0117] (2) Preparation of porous cracking catalyst

[0118] At 60°C, firstly, pseudo-boehmite powder of model P-DF-03-LS (produced by Shandong Aluminum Co., Ltd., with a specific surface area of ​​257 m 2 / g, pore volume 0.32cm 3 / g) was mixed with deionized water, and phosphoric acid was added after stirring for 1 hour. After stirring for another 1 hour, silica sol was added. After stirring evenly, the template agent N,N-diisopropylethylamine was slowly added dropwise. In the mixed system, n(Al2O3):n(SiO2):n(P2O5):n(C8H 19 N):n(H2O) in a molar ratio of 1:0.3:0.5:1.0:30. After the template agent is added dropwise, the mixed system is stirred for 1 hour at 60°C to obtain a gel mixture. The gel mixture is then transferred to a hydrothermal reactor with a polytetrafluoroethylene liner for the first crystallization treatment. The temperature of the first crystallization treatment is 170°C and the time is 12 hours. The mixed slurry obtained after the first crystallization treatment is uniformly mixed with superporous silica gel A (the weight ratio of superporous silica gel to mixed slurry is 1:9.1) and subjected to a second crystallization treatment. The temperature of the second crystallization treatment is 170°C and the time is 60 hours. After the crystallization is completed, the solid product obtained by centrifugal filtration is washed 6 times with deionized water, the solid product is dried at 110°C for 10 hours, and then calcined at 550°C for 16 hours to obtain a mixed molecular sieve D.

[0119] 2.6 g of calcium nitrate was dissolved in 70 g of deionized water, 9.1 g of the above-mentioned mixed molecular sieve D was added, and the mixture was stirred at 50° C. for 6 h. The solid product obtained after removing moisture using a rotary evaporator was dried at 110° C. for 12 hours and calcined at 600° C. for 8 hours to obtain a porous cracking catalyst D.

[0120] Based on the total weight of the porous cracking catalyst D, the content of SAPO-18 molecular sieve was 56% by weight, the content of ultra-large pore silica gel was 35% by weight, and the content of calcium oxide was 9%.

[0121] The specific surface area of ​​porous cracking catalyst D is 445 m 2 / g, pore volume 0.76cm 3 / g, and the most probable pore sizes are 0.41nm, 3.2nm and 29nm respectively.

[0122] The reaction performance of Catalyst D was tested using the same reaction performance evaluation method for direct conversion of waste plastics to light olefins as in step (3) of Example 1. The evaluation results are listed in Table 1.

[0123] Example 5

[0124] This embodiment is intended to illustrate the porous cracking catalyst prepared by the present invention and its application in the reaction of producing light olefins from waste plastics.

[0125] Ultra-macroporous silica gel B was prepared in the same manner as step (1) in Example 2.

[0126] (2) Preparation of porous cracking catalyst

[0127] At 40°C, the German imported pseudo-boehmite powder (model SB, purchased from Beijing Asia Pacific Aohua Chemical Additives Co., Ltd., with a specific surface area of ​​241 m 2 / g, pore volume 0.53cm 3 / g) was mixed with deionized water, and phosphoric acid was added after stirring for 1 hour. After stirring for another 1 hour, silica sol was added. After stirring evenly, the template agent N,N-diisopropylethylamine was slowly added dropwise. In the mixed system, n(Al2O3):n(SiO2):n(P2O5):n(C8H 19 N):n(H2O) in a molar ratio of 1:1.0:1.2:2.0:80. After the template agent is added dropwise, the mixed system is stirred for 3 hours at 40°C to obtain a gel mixture. The gel mixture is then transferred to a hydrothermal reactor with a polytetrafluoroethylene liner for the first crystallization treatment. The temperature of the first crystallization treatment is 160°C and the time is 16 hours. The mixed slurry obtained after the first crystallization treatment is uniformly mixed with superporous silica gel B (the weight ratio of superporous silica gel to mixed slurry is 1:3.8) and subjected to a second crystallization treatment. The temperature of the second crystallization treatment is 160°C and the time is 72 hours. After the crystallization is completed, the solid product obtained by centrifugal filtration is washed 8 times with deionized water, the solid product is dried at 130°C for 3 hours, and then calcined at 600°C for 8 hours to obtain a mixed molecular sieve E.

[0128] 1.9 g of magnesium nitrate hexahydrate was dissolved in 150 g of deionized water, 9.7 g of the above-mentioned mixed molecular sieve E was added, and the mixture was stirred at 90° C. for 2 h. The solid product obtained after removing moisture using a rotary evaporator was dried at 120° C. for 4 hours and calcined at 650° C. for 5 hours to obtain a porous cracking catalyst E.

[0129] Based on the total weight of the porous cracking catalyst E, the content of SAPO-18 molecular sieve is 32% by weight, the content of ultra-large pore silica gel is 65% by weight, and the content of magnesium oxide is 3%.

[0130] The specific surface area of ​​porous cracking catalyst E is 388m 2 / g, pore volume 1.0cm 3 / g, and the most probable pore sizes are 0.42nm, 3.3nm and 32nm respectively.

[0131] The reaction performance of porous cracking catalyst E was tested using the same reaction performance evaluation method for direct conversion of waste plastics to light olefins as in step (3) of Example 1. The evaluation results are listed in Table 1.

[0132] Example 6

[0133] This embodiment is intended to illustrate the porous cracking catalyst prepared by the present invention and its application in the reaction of producing light olefins from waste plastics.

[0134] Ultra-large pore silica gel A was prepared in the same manner as step (1) in Example 1.

[0135] (2) Preparation of porous cracking catalyst

[0136] At 60°C, firstly, pseudo-boehmite powder of model P-DF-03-LS (produced by Shandong Aluminum Co., Ltd., with a specific surface area of ​​257 m 2 / g, pore volume 0.32cm 3 / g) was mixed with deionized water, and phosphoric acid was added after stirring for 1 hour. After stirring for another 1 hour, silica sol was added. After stirring evenly, the template agent N,N-diisopropylethylamine was slowly added dropwise. In the mixed system, n(Al2O3):n(SiO2):n(P2O5):n(C8H 19 N):n(H2O) in a molar ratio of 1:0.2:0.4:0.8:25. After the template agent is added dropwise, the mixed system is stirred for 1 hour at 60°C to obtain a gel mixture. The gel mixture is then transferred to a hydrothermal reactor with a polytetrafluoroethylene liner for the first crystallization treatment. The temperature of the first crystallization treatment is 170°C and the time is 12 hours. The mixed slurry obtained after the first crystallization treatment is uniformly mixed with superporous silica gel A (the weight ratio of superporous silica gel to mixed slurry is 1:10.7) and subjected to a second crystallization treatment. The temperature of the second crystallization treatment is 170°C and the time is 60 hours. After the crystallization is completed, the solid product obtained by centrifugal filtration is washed 6 times with deionized water, the solid product is dried at 110°C for 10 hours, and then calcined at 550°C for 16 hours to obtain a mixed molecular sieve F.

[0137] 2.9 g of calcium nitrate was dissolved in 60 g of deionized water, 9.0 g of the above-mentioned mixed molecular sieve F was added, and the mixture was stirred at 50° C. for 6 h. The solid product obtained after removing moisture using a rotary evaporator was dried at 110° C. for 12 hours and calcined at 600° C. for 8 hours to obtain a porous cracking catalyst F.

[0138] Based on the total weight of the porous cracking catalyst F, the content of SAPO-18 molecular sieve is 60% by weight, the content of ultra-large pore silica gel is 30% by weight, and the content of calcium oxide is 10%.

[0139] The specific surface area of ​​porous cracking catalyst F is 450 m2 / g, pore volume 0.68cm 3 / g, and the most probable pore sizes are 0.41nm, 3.1nm and 28nm respectively.

[0140] The reaction performance of Catalyst F was tested using the same reaction performance evaluation method for direct conversion of waste plastics to light olefins as in step (3) of Example 1. The evaluation results are listed in Table 1.

[0141] Example 7

[0142] This embodiment is intended to illustrate the porous cracking catalyst prepared by the present invention and its application in the reaction of producing light olefins from waste plastics.

[0143] Ultra-macroporous silica gel B was prepared in the same manner as step (1) in Example 2.

[0144] (2) Preparation of porous cracking catalyst

[0145] At 40°C, the German imported pseudo-boehmite powder (model SB, purchased from Beijing Asia Pacific Aohua Chemical Additives Co., Ltd., with a specific surface area of ​​241 m 2 / g, pore volume 0.53cm 3 / g) was mixed with deionized water, and phosphoric acid was added after stirring for 1 hour. After stirring for another 1 hour, silica sol was added. After stirring evenly, the template agent N,N-diisopropylethylamine was slowly added dropwise. In the mixed system, n(Al2O3):n(SiO2):n(P2O5):n(C8H 19 N):n(H2O) in a molar ratio of 1:1.2:1.5:2.4:85. After the template agent is added dropwise, the mixed system is stirred for 3 hours at 40°C to obtain a gel mixture. The gel mixture is then transferred to a hydrothermal kettle with a polytetrafluoroethylene liner for the first crystallization treatment. The temperature of the first crystallization treatment is 160°C and the time is 16 hours. The mixed slurry obtained after the first crystallization treatment is uniformly mixed with superporous silica gel B (the weight ratio of superporous silica gel to mixed slurry is 1:2.9) and subjected to a second crystallization treatment. The temperature of the second crystallization treatment is 160°C and the time is 72 hours. After the crystallization is completed, the solid product obtained by centrifugal filtration is washed 8 times with deionized water, the solid product is dried at 130°C for 3 hours, and then calcined at 600°C for 8 hours to obtain a mixed molecular sieve G.

[0146] 1.3 g of magnesium nitrate hexahydrate was dissolved in 180 g of deionized water, 9.8 g of the above-mentioned mixed molecular sieve G was added, and the mixture was stirred at 90° C. for 2 h. The solid product obtained after removing moisture using a rotary evaporator was dried at 120° C. for 4 hours and calcined at 650° C. for 5 hours to obtain a porous cracking catalyst G.

[0147] Based on the total weight of the porous cracking catalyst G, the content of SAPO-18 molecular sieve is 28% by weight, the content of ultra-large pore silica gel is 70% by weight, and the content of magnesium oxide is 2%.

[0148] The specific surface area of ​​porous cracking catalyst G is 380m 2 / g, pore volume 1.05cm 3 / g, and the most probable pore sizes are 0.42nm, 3.3nm and 33nm respectively.

[0149] The reaction performance of porous cracking catalyst G was tested using the same reaction performance evaluation method for direct conversion of waste plastics to light olefins as in step (3) of Example 1. The evaluation results are listed in Table 1.

[0150] Comparative Example 1

[0151] Ultra-large pore silica gel A was prepared in the same manner as step (1) in Example 1.

[0152] (2) Preparation of porous cracking catalyst

[0153] At 60°C, firstly, pseudo-boehmite powder of model P-DF-03-LS (produced by Shandong Aluminum Co., Ltd., with a specific surface area of ​​257 m 2 / g, pore volume 0.32cm 3 / g) was mixed with deionized water, and phosphoric acid was added after stirring for 1 hour. After stirring for another 1 hour, silica sol was added. After stirring evenly, the template agent N,N-diisopropylethylamine was slowly added dropwise. In the mixed system, n(Al2O3):n(SiO2):n(P2O5):n(C8H 19 N):n(H2O) in a molar ratio of 1:0.6:0.9:1.6:60. After the template agent is added dropwise, the mixed system is stirred for 1 hour at 60°C to obtain a gel mixture. The gel mixture is then transferred to a hydrothermal reactor with a polytetrafluoroethylene liner for the first crystallization treatment. The temperature of the first crystallization treatment is 170°C and the time is 12 hours. The mixed slurry obtained after the first crystallization treatment is uniformly mixed with superporous silica gel A (the weight ratio of superporous silica gel to mixed slurry is 1:0.5) and subjected to a second crystallization treatment. The temperature of the second crystallization treatment is 170°C and the time is 60 hours. After the crystallization is completed, the solid product obtained by centrifugal filtration is washed 6 times with deionized water, the solid product is dried at 110°C for 10 hours, and then calcined at 550°C for 16 hours to obtain a mixed molecular sieve D1.

[0154] 2.4 g of strontium nitrate was dissolved in 50 g of deionized water, 8.8 g of the above-mentioned mixed molecular sieve D1 was added, and the mixture was stirred at 50°C for 6 h. The solid product obtained after removing moisture using a rotary evaporator was dried at 110°C for 12 hours and calcined at 600°C for 8 hours to obtain a porous cracking catalyst D1.

[0155] Based on the total weight of the porous cracking catalyst D1, the content of SAPO-18 molecular sieve is 6% by weight, the content of ultra-large pore silica gel is 82% by weight, and the content of strontium oxide is 12%.

[0156] The specific surface area of ​​porous cracking catalyst D1 is 318 m 2 / g, pore volume 1.33cm 3 / g.

[0157] The reaction performance of the porous cracking catalyst D1 was tested using the same reaction performance evaluation method for direct conversion of waste plastics to light olefins as in step (3) of Example 1. The evaluation results are listed in Table 1.

[0158] Comparative Example 2

[0159] Ultra-macroporous silica gel B was prepared in the same manner as step (1) in Example 2.

[0160] (2) Preparation of porous cracking catalyst

[0161] At 40°C, the German imported pseudo-boehmite powder (model SB, purchased from Beijing Asia Pacific Aohua Chemical Additives Co., Ltd., with a specific surface area of ​​241 m 2 / g, pore volume 0.53cm 3 / g) was mixed with deionized water, and phosphoric acid was added after stirring for 1 hour. After stirring for another 1 hour, silica sol was added. After stirring evenly, the template agent N,N-diisopropylethylamine was slowly added dropwise. In the mixed system, n(Al2O3):n(SiO2):n(P2O5):n(C8H 19 N):n(H2O) in a molar ratio of 1:0.4:0.7:1.3:50. After the template agent is added dropwise, the mixed system is stirred for 3 hours at 40°C to obtain a gel mixture. The gel mixture is then transferred to a hydrothermal kettle with a polytetrafluoroethylene liner for the first crystallization treatment. The temperature of the first crystallization treatment is 160°C and the time is 16 hours. The mixed slurry obtained after the first crystallization treatment is uniformly mixed with superporous silica gel B (the weight ratio of superporous silica gel to mixed slurry is 1:32) and subjected to a second crystallization treatment. The temperature of the second crystallization treatment is 160°C and the time is 72 hours. After the crystallization is completed, the solid product obtained by centrifugal filtration is washed 8 times with deionized water, the solid product is dried at 130°C for 3 hours, and then calcined at 600°C for 8 hours to obtain a mixed molecular sieve D2.

[0162] 0.2 g of barium nitrate was dissolved in 200 g of deionized water, 9.9 g of the above-mentioned mixed molecular sieve D2 was added, and the mixture was stirred at 90°C for 2 h. The solid product obtained after removing moisture using a rotary evaporator was dried at 120°C for 4 hours and calcined at 650°C for 5 hours to obtain a porous cracking catalyst D2.

[0163] Based on the total weight of the porous cracking catalyst D2, the content of SAPO-18 molecular sieve was 81% by weight, the content of ultra-large pore silica gel was 18% by weight, and the content of barium oxide was 1%.

[0164] The specific surface area of ​​porous cracking catalyst D2 is 511m 2 / g, pore volume 0.45cm 3 / g.

[0165] The reaction performance of the porous cracking catalyst D2 was tested using the same reaction performance evaluation method for direct conversion of waste plastics to light olefins as in step (3) of Example 1. The evaluation results are listed in Table 1.

[0166] Comparative Example 3

[0167] Ultra-large pore silica gel A was prepared in the same manner as step (1) in Example 1.

[0168] Eliminate step (2) in Example 1.

[0169] The reaction performance of ultra-large pore silica gel A was tested using the same reaction performance evaluation method for direct conversion of waste plastics to light olefins as in step (3) of Example 1. The evaluation results are listed in Table 1.

[0170] Comparative Example 4

[0171] The catalyst was prepared in the same manner as in Example 1, except that:

[0172] Cancel step (1) in Example 1.

[0173] The specific process of preparing SAPO-18 molecular sieve is as follows:

[0174] At 60°C, firstly, pseudo-boehmite powder of model P-DF-03-LS (produced by Shandong Aluminum Co., Ltd., with a specific surface area of ​​257 m 2 / g, pore volume 0.32cm 3 / g) was mixed with deionized water, and phosphoric acid was added after stirring for 1 hour. After stirring for another 1 hour, silica sol was added. After stirring evenly, the template agent N,N-diisopropylethylamine was slowly added dropwise. In the mixed system, n(Al2O3):n(SiO2):n(P2O5):n(C8H 19N):n(H2O) in a molar ratio of 1:0.6:0.9:1.6:60. After the template agent is added dropwise, the mixed system is stirred at 60°C for 1 hour to obtain a gel mixture. The gel mixture is then transferred to a hydrothermal kettle with a polytetrafluoroethylene liner for crystallization. The crystallization temperature is 170°C and the time is 72 hours. After the crystallization is completed, the solid product obtained by centrifugation is washed 6 times with deionized water, the solid product is dried at 110°C for 10 hours, and then calcined at 550°C for 16 hours to obtain SAPO-18 molecular sieve.

[0175] The specific surface area of ​​SAPO-18 molecular sieve is 558m 2 / g, pore volume 0.24cm 3 / g.

[0176] The reaction performance of SAPO-18 molecular sieve was tested by the same reaction performance evaluation method for direct conversion of waste plastics to light olefins as in step (3) of Example 1. The evaluation results are listed in Table 1.

[0177] Comparative Example 5

[0178] The SAPO-18 molecular sieve was prepared according to the method of Comparative Example 4.

[0179] 1.8 g of calcium nitrate was dissolved in 100 g of deionized water, 9.4 g of the above-mentioned SAPO-18 molecular sieve was added, and the mixture was stirred at 50° C. for 6 h. The solid product obtained after removing moisture using a rotary evaporator was dried at 110° C. for 12 hours and calcined at 600° C. for 8 hours to obtain cracking catalyst D3.

[0180] Based on the total weight of the cracking catalyst D3, the content of SAPO-18 molecular sieve was 94% by weight, and the content of calcium oxide was 6%.

[0181] The specific surface area of ​​cracking catalyst D3 is 518m 2 / g, pore volume 0.21cm 3 / g.

[0182] The reaction performance of cracking catalyst D3 was tested using the same reaction performance evaluation method for direct conversion of waste plastics to light olefins as in step (3) of Example 1. The evaluation results are listed in Table 1.

[0183] Comparative Example 6

[0184] The catalyst was prepared in the same manner as in Example 1, except that:

[0185] Cancel step (1) in Example 1.

[0186] Preparation of cracking catalyst D4, the specific process is as follows:

[0187] At 60°C, firstly, pseudo-boehmite powder of model P-DF-03-LS (produced by Shandong Aluminum Co., Ltd., with a specific surface area of ​​257 m 2 / g, pore volume 0.32cm 3 / g) was mixed with deionized water, and phosphoric acid was added after stirring for 1 hour. After stirring for another 1 hour, silica sol was added. After stirring evenly, the template agent N,N-diisopropylethylamine was slowly added dropwise. In the mixed system, n(Al2O3):n(SiO2):n(P2O5):n(C8H 19 N):n(H2O) in a molar ratio of 1:0.6:0.9:1.6:60. After the template agent is added, the mixed system is stirred for 1 hour at 60°C to obtain a gel mixture. The gel mixture is then transferred to a hydrothermal kettle with a polytetrafluoroethylene liner for the first crystallization treatment. The temperature of the first crystallization treatment is 170°C and the time is 12 hours. The mixed slurry obtained after the first crystallization treatment is mixed with silica powder (made in the laboratory, with a specific surface area of ​​274m 2 / g, pore volume 0.57cm 3 / g) were uniformly mixed (the weight ratio of ultra-large pore silica gel to mixed slurry was 1:6.4), and the second crystallization treatment was carried out. The temperature of the second crystallization treatment was 170°C and the time was 60h. After the crystallization was completed, the solid product obtained by centrifugal filtration was washed with deionized water 6 times, the solid product was dried at 110°C for 10h, and then calcined at 550°C for 16h to obtain a mixed molecular sieve.

[0188] 1.2 g of calcium nitrate was dissolved in 100 g of deionized water, 9.6 g of the above-mentioned mixed molecular sieve was added, and the mixture was stirred at 50° C. for 6 h. The solid product obtained after removing moisture using a rotary evaporator was dried at 110° C. for 12 hours and calcined at 600° C. for 8 hours to obtain cracking catalyst D4.

[0189] Based on the total weight of the cracking catalyst D4, the content of SAPO-18 molecular sieve was 45% by weight, the content of silicon dioxide was 51% by weight, and the content of calcium oxide was 4%.

[0190] The reaction performance of composite material D4 was tested by the same reaction performance evaluation method for direct conversion of waste plastics to light olefins as in step (3) of Example 1. The evaluation results are listed in Table 1.

[0191] Table 1

[0192]

[0193]

[0194] It can be seen from the above results that the porous cracking catalyst provided by the present invention can directly catalyze the conversion of waste plastics into light olefins. The conversion rate of waste plastics is 100%, and the yield of light olefins is high.

[0195] In Comparative Example 1, the content of ultra-large pore silica gel is too high, the content of SAPO-18 molecular sieve is too low, and the content of modified oxide is not within the range defined by the present invention. Due to the small number of acidic centers on the catalyst and insufficient activation sites during the reaction, the raw material conversion rate and the yield of light olefins are low.

[0196] In Comparative Example 2, the content of ultra-large pore silica gel is too low, the content of SAPO-18 molecular sieve is too high, and the content of modified oxide is significantly lower than the range defined in the present invention. Due to the small number of mesopores in the catalyst, the diffusion of reactant and product molecules is hindered during the reaction, and the occurrence of side reactions cannot be effectively suppressed, resulting in a low yield of light olefins.

[0197] In Comparative Example 3, only ultra-large pore silica gel was used as the cracking catalyst without adding SAPO-18 molecular sieve. Since there were almost no active acidic centers on the catalyst, the raw material conversion rate and the yield of light olefins were low.

[0198] In Comparative Example 4, only SAPO-18 molecular sieve was used as a cracking catalyst, and no ultra-large pore silica gel was added, and no modification treatment was performed. Since the catalyst does not contain mesoporous channels, the diffusion of reactants and product molecules is hindered during the reaction and the distribution of surface acidic centers is unreasonable, resulting in a low yield of light olefins.

[0199] In Comparative Example 5, only the modified SAPO-18 molecular sieve was used as the cracking catalyst without adding ultra-large pore silica gel. Since the catalyst does not contain mesoporous channels, the diffusion of reactants and product molecules is hindered during the reaction, resulting in a low yield of light olefins.

[0200] In Comparative Example 6, silicon dioxide powder is used instead of ultra-large pore silica gel. Since silicon dioxide has a lower specific surface area, a smaller pore volume, and an irregular pore structure, its dispersion effect is significantly lower than that of ultra-large pore silica gel, resulting in a lower yield of light olefins in the prepared cracking catalyst.

[0201] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A porous cracking catalyst, characterized in that: The porous cracking catalyst comprises SAPO-18 molecular sieve, ultra-large pore silica gel and modified oxide, and based on the total weight of the porous cracking catalyst, the content of the SAPO-18 molecular sieve is 28-60% by weight, the content of the ultra-large pore silica gel is 30-70% by weight, and the content of the modified oxide is 2-10% by weight; The specific surface area of ​​the porous cracking catalyst is 380-450m 2 / g, the pore volume is 0.68-1.05mL / g, the pore size distribution is a trimodal distribution, and the most probable pore sizes corresponding to the three peaks are 0.38-0.45nm, 2-4.5nm and 15-45nm, respectively.

2. The porous cracking catalyst according to claim 1, wherein Based on the total weight of the porous cracking catalyst, the content of the SAPO-18 molecular sieve is 32-56% by weight, the content of the ultra-large pore silica gel is 35-65% by weight, and the content of the modified oxide is 3-9% by weight; Preferably, based on the total weight of the porous cracking catalyst, the content of the SAPO-18 molecular sieve is 36-52% by weight, the content of the ultra-large pore silica gel is 40-60% by weight, and the content of the modified oxide is 4-8% by weight.

3. The porous cracking catalyst according to claim 1 or 2, wherein: The specific surface area of ​​the porous cracking catalyst is 388-445m 2 / g, pore volume is 0.76-1.00mL / g, pore size distribution is trimodal distribution, and the most probable pore sizes corresponding to the three peaks are 0.39-0.44nm, 2.5-4nm and 20-38nm respectively; More preferably, the specific surface area of ​​the porous cracking catalyst is 394-440m 2 / g, the pore volume is 0.84-0.93mL / g, the pore size distribution is a trimodal distribution, and the most probable pore sizes corresponding to the three peaks are 0.4-0.42nm, 2.8-3.4nm and 25-32nm, respectively.

4. The porous cracking catalyst according to claim 1 or 2, wherein: The modified oxide is selected from alkaline earth metal oxides; preferably, the modified oxide is selected from one or more of calcium oxide, magnesium oxide, strontium oxide and barium oxide.

5. The porous cracking catalyst according to claim 1 or 2, wherein: The specific surface area of ​​the ultra-large pore silica gel is 200-500m 2 / g, the pore volume is 1-2mL / g, the pore size is bimodal distribution, the first most probable pore size is 2-5nm, and the second most probable pore size is 20-50nm.

6. The porous cracking catalyst according to any one of claims 1 to 5, wherein: The preparation method of the ultra-macroporous silica gel comprises: In the presence of butanol and propylene glycol, an inorganic silicon source is contacted with an acid agent, and the obtained mixture is filtered and washed to obtain a silica gel filter cake; the silica gel filter cake is then dried, calcined and ball-milled to obtain ultra-large-porous silica gel.

7. The porous cracking catalyst according to claim 6, wherein: The inorganic silicon source is selected from one or more of water glass, sodium metasilicate and silica sol; And / or, the weight ratio of the inorganic silicon source, acid agent, butanol and glycerol is 1: (0.05-0.5): (0.02-0.6): (0.02-0.6), preferably 1: (0.1-0.3): (0.06-0.4): (0.06-0.4).

8. A method for preparing a porous cracking catalyst according to any one of claims 1 to 7, characterized in that: The preparation method comprises: (1) mixing a template, an aluminum source, a phosphorus source, a silicon source and water and performing a contact reaction to obtain a gel mixture; performing a first crystallization treatment on the gel mixture to obtain a mixed slurry, mixing the mixed slurry with ultra-large pore silica gel and performing a second crystallization treatment, and separating, washing, drying and calcining the product after the crystallization treatment to obtain a mixed molecular sieve; (2) The mixed molecular sieve is immersed in an aqueous solution containing a modified oxide precursor, and the solid product after water removal is dried and calcined to obtain a porous cracking catalyst.

9. The preparation method according to claim 8, wherein: In step (1), the template agent is N,N-diisopropylethylamine; And / or, the aluminum source is selected from one or more of pseudo-boehmite, aluminum hydroxide, basic aluminum sol, aluminum isopropoxide, basic aluminum acetate, gibbsite and boehmite; And / or, the phosphorus source is an inorganic acid or acid salt containing phosphorus, preferably one or more of phosphoric acid, phosphorous acid, diammonium phosphate and monoammonium phosphate; And / or, the silicon source is an organic silicon source and / or an inorganic silicon source, preferably one or more of tetramethyl silicate, tetraethyl silicate, tetraisopropyl silicate, tetrabutyl silicate, silica sol, water glass and white carbon black; And / or, the molar ratio of the aluminum source (in terms of Al2O3), the silicon source (in terms of SiO2), the phosphorus source (in terms of P2O5), the template and water is 1: (0.1-2): (0.2-2.5): (0.5-3): (10-150); And / or, the weight ratio of the ultra-large pore silica gel to the mixed slurry is 1:(2-15), preferably 1:(3-10).

10. The preparation method according to claim 8, wherein: The conditions of the contact reaction include: a temperature of 20-100°C, preferably 40-80°C; And / or, the conditions of the first crystallization include: temperature of 140-200° C., time of 2-24 h; And / or, the conditions of the second crystallization include: temperature of 140-200° C., time of 20-100 h; And / or, the calcination conditions include: temperature of 450-650° C. and time of 5-50 h.

11. The preparation method according to claim 8, wherein: In step (2), the modified oxide precursor is an inorganic salt of an alkaline earth metal; preferably, the alkaline earth metal is selected from one or more of calcium, magnesium, strontium and barium; And / or, the mass concentration of the aqueous solution containing the modified oxide precursor is 0.3-5%; and / or, the weight ratio of the mixed molecular sieve to the aqueous solution containing the modified oxide precursor is 1:(5-20); And / or, the calcination conditions include: temperature of 500-700° C. and time of 3-20 h.

12. Use of the porous cracking catalyst according to any one of claims 1 to 7 in the direct catalytic cracking of waste plastics to produce light olefins.

13. The use according to claim 12, wherein: The application comprises: contacting waste plastic powder or particles with the porous cracking catalyst to react; And / or, the contact conditions include: temperature of 420-580°C, pressure of 0.01-1MPa, and contact time of 0.5-12h; And / or, the weight ratio of the porous cracking catalyst to the waste plastic powder or particles is 1:(0.5-50).

Citation Information

Patent Citations

  • Method for recovering styrene and other aromatic hydrocarbon raw materials by catalyzing and cracking waste polystyrene

    CN101891581A

  • Multistage-pore molecular sieve catalyst for transforming waste plastics and preparation method therefor

    CN105214716A

  • A catalytic process of simultaneous pyrolysis of mixed plastics and dechlorination of the pyrolysis oil

    CN109563413A

  • Oxidative cracking of hydrocarbons

    US11046892B1

  • Use of a catalyst composition for the catalytic depolymerization of plastics waste

    US20180361356A1